2017
DOI: 10.17977/um031v3i22017p123
|View full text |Cite
|
Sign up to set email alerts
|

Meningkatkan Kemampuan Membaca Pemahaman Anak Tunagrahita Ringan dengan Menggunakan Metode Reading Aloud

Abstract: Penelitian ini bertujuan untuk mengetahui adanya pengaruh metode reading aloud terhadap kemampuan membaca pemahaman anak tunagrahita ringan kelas VI. Penelitian ini merupakan jenis penelitian kuantitatif, dengan jenis penelitian Pre-Eksperimental dengan One-Group Pre-test Post-test Design menggunakan rumus uji Wilcoxon. Subjek berjumlah 6 anak. Pengumpulan data menggunakan tes soal pemahaman. Berdasarkan hasil pengujian data statistik diperoleh 0,023<0,05 maka H 1 diterima. Kesimpulan dari penelitian ini adala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…In addition, Hardianto revealed a significant improvement in third-grade elementary school students' reading ability due to the application of the method (Hardianto, 2019). Moreover, Akta Sunci Mahartika and Dimas Arif Dewantoro also investigated how the Read-Aloud method improved reading skills in children with special needs (Mahartika & Dewantoro, 2017). Even more, a study conducted by Jennifer Kohart Marchessault and Karen H. Larwin revealed that the Read-Aloud method could improve children's vocabulary mastery (Marchessault & Larwin, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Hardianto revealed a significant improvement in third-grade elementary school students' reading ability due to the application of the method (Hardianto, 2019). Moreover, Akta Sunci Mahartika and Dimas Arif Dewantoro also investigated how the Read-Aloud method improved reading skills in children with special needs (Mahartika & Dewantoro, 2017). Even more, a study conducted by Jennifer Kohart Marchessault and Karen H. Larwin revealed that the Read-Aloud method could improve children's vocabulary mastery (Marchessault & Larwin, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Selain itu, metode membaca dengan nyaring juga dapat meningkatkan keterampilan membaca pada anak retardasi mental ringan. Hal tersebut dibuktikan oleh Mahartika & Dewantoro, (2017), dari hasil penelitiannya yang menunjukkan adanya pengaruh yang signifikan dari metode membaca nyaring terhadap kemampuan pemahaman yang dimiliki oleh subjek. Selain itu, pelatihan kesadaran persepsi visual juga dapat meningkatkan kemampuan pra membaca anak retardasi mental ringan.…”
Section: Pembahasanunclassified
“…Education is ideally something that is very important in developing attitudes and skills (Astalini et al, 2018;Campbell et al, 2017;Putri et al, 2020). Quality education is a picture of the success of a nation (Duma et al, 2021;Joarder et al, 2020;Mahartika & Dewantoro, 2017). Education is good for learning success if learning goes well then education will follow.…”
Section: Introductionmentioning
confidence: 99%